Learning Designing for Establishment Physics Content and Teacher Pedagogic Aspects Through Lesson Study-based In-House Training - Adam Malik; Seni Susanti (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2021)
Mastering physics content is essential for physics teachers to carry out the learning process in the classroom. After mastering good physics content, teachers must also master the teaching competencies contained in pedagogical competencies. This study aims to demonstrate efforts to increase teachers' mastery of physics content and pedagogic competence. The pedagogic aspect refers to the teacher's ability to prepare practical instructions in a Cookbook Laboratory, Inquiry Laboratory, Problem-Solving Laboratory, and Higher Order Thinking Laboratory. The method used is in-house training based on lesson study. There are three stages of activities carried out, including Plan, Do, and See. Data were collected using observation sheets, interview guidelines, performance instruments, and tests. The study results show that the professional competence of teachers who are members of the Science Teacher Deliberation (MGMP) in one province in West Java has increased, especially concerning materials competencies practiced. In addition, the pedagogical competence of the teachers who are members of the Science MGMP has increased, especially concerning the mastery of organizing science practicums oriented to developing the 21st-century skills of students.